ANALISIS KOMPETENSI PEDAGOGIK GURU PADA PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENUNJANG TUGAS ADMINISTRASI PEMBELAJARAN DI TK ISLAM AL IZHAR CENDEKIA MAKASSAR - Witri Ali; Muh. Ardiansyah; Kartini Marzuki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze teachers’ pedagogical competence in utilizing Information and Communication Technology (ICT) to support learning administration tasks at Al Izhar Cendekia Islamic Kindergarten Makassar. The background of this research is based on the importance of integrating ICT into early childhood education as an effort to improve the quality of learning and administrative effectiveness. This research employed a qualitative approach with data collected through observation, interviews, and documentation. The results indicate that the teachers at Al Izhar Cendekia Islamic Kindergarten possess good pedagogical competence in designing, implementing, and evaluating early childhood learning. They have also begun to integrate ICT into both teaching and administrative processes in a selective and contextual manner. ICT tools such as Microsoft Office, Google Drive, and Canva are used in lesson planning, documenting student development, and communication with parents. Supporting factors for ICT utilization include principal support, regular training, the availability of technological devices, and a collaborative work culture. In contrast, inhibiting factors include limited technical skills among teachers, unstable internet connectivity, and challenges in time management.